Service Quality Terhadap Repurchase Intention di Mediasi Oleh Customer Satisfaction - Nunuk Maf'idayu; Amelindha Vania (Universitas Islam Kadiri, 2022)
This study aims to determine the effect of service quality on repurchase intention mediated by customer satisfaction on consumers of Kopi Hashtag Dau, Malang. The type of research used is quantitative research. The research location appointed by the researcher is the consumers of Café Kopi Hashtag which is located on Jl. Raya Dermo No. 137-177, Jetak Lor, Mulyoagung, Dau, Malang. The number of samples in this study were 100 respondents. The sample of this research is Hashtag Coffee consumers aged 17 years and over who have visited Hashtag Coffee at least once. The variables used in this study consisted of independent variables, dependent variables, and intervening variables. The dependent variable is repurchase intention, the independent variable is service quality and the intervening variable is customer satisfaction. The data that has been obtained were analyzed using SmartPLS Version 3. Based on the research results obtained, it can be concluded that (1) service quality has a significant positive effect on customer satisfaction, (2) customer satisfaction has a significant positive effect on repurchase intention, (3) service quality has a positive effect significant impact on repurchase intention, (4) service quality has a significant positive effect on repurchase intention mediated by customer satisfaction.